Anxiety and Aggressive Behavior in Adolescents: A Correlational Study - Febriana Sartika Sari; Sulistyaningsih Sulistyaningsih; Intan Maharani Sulistyawati Batubara; Megan J Eagle; Ratna Wirawati Rosyida (IJNP (Indonesian Journal of Nursing Practices), 2022)
Background: Aggressive behavior has become a severe behavioral problem in adolescents recently. Some cases have even been deemed an emergency for mental health behavior in adolescents. Many factors are suspected to be associated with aggressive behavior, one of which is anxiety. Anxiety and aggressive behavior remain widely studied in children, but the number of studies is limited to middle and late adolescents. In addition, there is no clear description of the psychosocial aspects between anxiety and aggressive behavior in adolescents based on the psychosocial development tasks. Objective: The study aims to identify the association between adolescents’ anxiety and aggressive behavior.Methods: The research used an analytical correlation design with a cross-sectional approach. The research was conducted in senior high schools in Surakarta in July 2021. Subjects were taken using convenience sampling, in which 626 students filled out the online questionnaire, while 32 students did not complete some items resulting in a total sample of 594 respondents. Then, the research instruments employed DASS 21 for anxiety and Buss Perry Questionnaire for aggressive behavior. The statistical analysis then utilized the Pearson product-moment test.Results: The research revealed that most respondents were female (67,8%). The respondents had a bullying victim history (44.8%), a violence victim history (13.3%), and parental divorce history (10.3%). The statistical test also uncovered a significant correlation between anxiety and aggressive behavior (p-value 0.0001, r: 0.649, OR:7.86, CI 95%).Conclusion: The finding demonstrates the association between adolescents’ anxiety and aggressive behavior. Consequently, the community mental health nurses should organize a partnership mental health program with the senior high schools to manage adolescent anxiety and aggressive behavior